Surface anticoagulation of mechanical heart valves using electrically induced biomimetic glycocalyx: An in-vitro study to assess hemocompatibility and optimal voltage - Lokeswara Rao Sajja; Aditya Koppula; Thomas Mathew; Anugya Bhatt (PLoS ONE, 2026)
Mechanical heart valves (MHVs) remain the most durable option for valve replacement, but they are highly thrombogenic and therefore necessitate life-long anticoagulation. We designed a novel MHV assembly based on “Surface Anticoagulation by Electrically induced Biomimetic Glycocalyx” (SAEBG) that imposes a weak negative potential across the valve’s blood-contacting surfaces using an implantable pacemaker as an energy source. The concept is inspired by the native vascular endothelium, where the luminal glycocalyx carries a net negative surface charge that repels platelets and proteins. The present study aims to assess hemocompatibility and thromboresistance in our electrically activated MHV. Bileaflet MHVs (n = 9) were immersed in human platelet-rich plasma or whole blood, of which 5 valves were connected to a programmable pulse generator. Control valves (0 V) (n = 4) were compared to those activated at 0.25 (n = 3), and 0.5 V(n = 2). The control/activated valves were immersed in PRP/blood for 30 min under gentle agitation at 35 ± 2 °C. Hemolysis and blood cell integrity in the supernatant fluid were quantified using standard hematology analyses. Valves immersed in PRP were assessed by scanning electron microscopy (SEM). The cell/deposit free area as assessed by SEM was highest with 0.5 V (~96%), while the corresponding free areas for controls and 0.25 V were ~86% and ~58%, respectively. The platelet counts, platelet and coagulation markers were close to the measurement uncertainty ranges for all the experiments. Hemolysis was < 0.1% for all conditions, and the leucocyte and red-cell counts changed by <2%. Imposing a mild electrical potential (~0.5 V) on an MHV reproduces the anti-thrombotic behaviour of vascular endothelium. The electrical field did not injure blood cells or activate coagulation pathways, establishing a safe and effective voltage window for the SAEBG valve to enable further swine model experiments.